Cumulative consumption of tea is associated with lower risk of liver cancer: Updated results from the Shanghai Women's Health Study. Issue 6 (14th October 2022) - Li, Zhuo‐Ying; Tan, Yu‐Ting; Liu, Da‐Ke; Gao, Li‐Feng; Li, Hong‐Lan; Xiang, Yong‐Bing
Abstract: Prospective epidemiological studies have provided limited evidence for an association between tea consumption and liver cancer risk. Based on a population‐based prospective cohort study in middle‐aged Chinese women, we investigated the association between tea consumption and the risk of primary liver cancer. Detailed information on tea drinking habits and other potential confounders was obtained at the baseline interview. Incident liver cancer cases were identified through record linkage with the population‐based cancer registry and verified through home visits and review of medical charts by medical experts. Multiple aspects of tea drinking habits including starting age, duration, intensity and cumulative consumption of any type of tea and green tea were considered. Multivariable‐adjusted hazard ratios (aHRs) and their 95% confidence intervals (CIs) were derived from the Cox regression models. After a median follow‐up time of 18.12 (interquartile range = 1.59) years, 253 incident liver cancer cases were identified from 71 841 cohort members. Compared with never tea drinkers, the risk of liver cancer for participants who have consumed over 30 kg of dried tea leaves cumulatively was 0.56 (95% CI: 0.32‐0.97). For those who drank green tea only, the aHR was 0.54 (95% CI: 0.30‐0.98). This updated study suggested an inverse association between cumulative consumption of tea, especially green tea and the risk of primary liver cancer. Abstract : What's new? Previous epidemiological studies have reached inconsistent conclusions regarding the association between tea consumption and liver cancer risk. Using data from a population‐based prospective cohort study in middle‐aged Chinese women, here the authors investigated the associations between multiple aspects of tea drinking habits and the risk of primary liver cancer. The findings highlighted the importance of cumulative consumption of tea, not just the intensity of tea consumption. The study showed that greater cumulative consumption of dried tea leaves was associated with a lower risk of liver cancer.